Pengaruh Metode Pengolahan Kopi Robusta Gumitir Di Kabupaten Jember Terhadap Karakteristik Green Coffee Powder (GCP) - Nuraisyah, Anni; Suandri, Afina (Agropross : National Conference Proceedings of Agriculture, 2023)
Coffee is a plantation crop commodity that is widely consumed in Indonesia as a refreshing drink. Broadly speaking, coffee processing methods include natural processing, honey processing, semi-wet processing, and wet methods. Green coffee powder (GCP) is unroasted coffee that is ground to a certain particle size. Green coffee powder as a new product processed from green coffee without roasting, so in the processing process it is necessary to analyze the profile of green coffee beans. The differences in the processing methods of natural process coffee, honey process, semi wet process, and wet process are related to the physical and chemical characteristics of green coffee powder. GCP began to be recognized by the public because of its benefits as a functional food product that can increase body metabolism and lose weight. The research method used is Non Factorial Complete Randomized Design (RAL Non Factorial) and descriptive method. The treatment consisted of 4 processing methods, namely natural process, honey process, semi wet process, and wet process, so that 4 treatments were obtained with 5 replicates and 20 experimental units were obtained. The data were analyzed using the ANOVA analysis of variance method and continued with the BNT further test with a confidence level of 95%. The results showed a very significant difference from the effect of processing methods on the parameters of camba density and moisture content. While the effect of processing method did not give a significant difference to the parameters of yield and pH produced. In addition, from the results of chemical characteristics research, there are differences in the amount of caffeine content and volatile compounds from each processing method. Of these compounds that give the strongest aroma to green coffee powder is the compound Pyrazine, methyl- (CAS) Methylpyrazine.